GreenLight HPS™ 120‐W laser vaporization vs transurethral resection of the prostate (<60 mL): a 2‐year randomized double‐blind prospective urodynamic investigation - Pereira‐Correia, João Antonio; de Moraes Sousa, Karlo Danilson; Santos, João Bosco Pinheiro; de Morais Perpétuo, Daniel; Lopes‐da‐Silva, Luiz Felipe; Krambeck, Renato Lages; Muller, Valter José Fernandes; Vaz, Fernando Pires (BJU international, 2012)
Study Type – Therapy (RCT) Level of Evidence 1b What's known on the subject? and What does the study add? Photovaporization of the prostate (PVP) is now challenging TURP as the standard treatment for lower LUTS caused by BPH. The learning curve for PVP is short and the main advantages of this method over TURP are a shorter period of hospitalization, a shorter period of postoperative vesical catheterization, lower levels of retrograde ejaculation, rare development of dilutional hyponatraemia syndrome, the lack of a need for postoperative vesical irrigation as a result of extremely low indices of postoperative haematuria, and the lack of a need to suspend anticoagulant medication for the surgery. Traditionally, comparisons of the effectiveness of TURP vs PVP have involved parameters such as peak flow urinary rate and post‐void residual urine volume measurements, and have employed questionnaires such as the IPSS and the International Index of Erectile Function instruments. However, studies evaluating detailed urodynamic parameters remain scarce and non‐comparative The present study compared postoperative, medium‐term urodynamic parameters among patients receiving TURP and high‐power PVP. We consider the present study to be distinctive because it involved a double‐blind, detailed functional analysis of the vesical emptying stage over the course of 2 years, and did not simply comprise an evaluation of clinical parameters and uroflowmetrics. We saw a reduction of infravesical obstruction, as shown by the significant reduction of ≥20 cm H2O in the mean micturition pressure for the groups studied, as well as a significant reduction in bladder outlet obstruction index. Thus, the present data show that high‐power PVP can achieve and maintain the same results as TURP over a period of 24 months regarding an aspect that is particularly important for maintaining vesical health (i.e. detrusor pressure during the evacuation of the bladder). Such urodynamic data describing the functional outcome of PVP are currently missing from the literature. OBJECTIVE • To assess the impact of GreenLight HPSTM 120‐W (American Medical System Incorporation, Minnetonka, MN, USA) laser photovaporization of the prostate (PVP) compared to transurethral resection of the prostate (TURP) on urodynamic results, voiding function and sexual function. PATIENTS AND METHODS • In total, 20 men with intermediate/severe lower urinary tract symptoms as a result of benign prostatic hyperplasia (BPH) were randomly selected and equally divided into two groups: TURP and PVP. • Urodynamic evaluation was performed and International Prostate Symptom Score (IPSS), International Index of Erectile Function‐5 and International Consultation on Incontinence Questionnaire – Short Form questionnaires were completed. • The results were assessed at 2 years. RESULTS • Mean IPSS scores were reduced in both groups, although they did not differ between the TURP and PVP groups. • There was no significant change in International Index of Erectile Function‐5 scores. • Half of the patients in the PVP group developed urge urinary incontinence with spontaneous resolution. • The urodynamic parameters analyzed showed an improvement for both groups, although the values in the TURP group values were not significantly different from those in the PVP group. CONCLUSIONS • Bladder storage symptoms may represent a major concern, although they are of limited duration in patients undergoing PVP. • High‐power PVP can achieve and maintain the same results as TURP over a period of 24 months.